A soberania estatal e os direitos humanos dos encarcerados : leitura da superlotação como ineficácia dos direitos humanos no cárcere brasileiro - Santos, Gustavo Henrique Queiroz dos (2020)
This dissertation analyzes the prison overcrowding as a reflection of a rigid Brazilian state sovereignty model, which results in the ineffectiveness of the human rights of prisioners. The objective is to understand how the state sovereignty model adopted by the Brazilian state contributes to the violation of human rights. The analysis does not intend to propose a model of sovereignty to be adopted by Brazil. The research problem is expressed in the following question: Does the sovereignty of the Brazilian state constitute an obstacle to the effectiveness of the prisoners’ human rights? The methodology used is exploratory and bibliographic in nature. The realistic perspective appears in the form of reading the prison reality and the concept of sovereignty. The theoretical framework results from an articulation between the concepts of sovereignty (BODIN, 2011) modern state (LOCKE, 1988) and effectiveness (KELSEN, 2009). As a result, the research aims to demonstrate that some human rights of those in incarceration are not effective due to the rigid state sovereignty model.